The Application of Abraham Maslow's Hierarchical Theory in Islamic Education Learning at Tamanan Elementary School Bantul - Adib, M. Afiqul; Suyadi, Suyadi (Program Studi Pendidikan Agama Islam, 2021)
This research aims to determine the application of Abraham Maslow's hierarchy of needs theory in Islamic education learning at Tamanan Elementary School Bantul to help teachers understand the desires of their students in learning. The method used is field research, then it is integrated with various related sources. The results of this study are: a) Maslow's hierarchy of needs theory b) Application of Abraham Maslow's Hierarchy of Needs (Humanistic) Theory in Islamic Education learning at Tamanan Elementary School. The conclusion of Maslow's theory of needs aims to make individuals as good human being as possible. This will be very useful in the application of learning so that students can understand themselves and their environment. The students who have reached this level will do various things in order to maximize their potential so that learning can be effective.